The short term impact of radiofrequency ablative techniques and peripheral nerve block on thermoregulation in mouse models - Tomoo Yuba; Yoshihisa Koyama; Yuki Kinishi; Yuji Fujino; Shoichi Shimada (Scientific Reports)
Abstract This study investigated the impact of multiple nerve block methods (local anesthesia, conventional radiofrequency thermocoagulation [CRF], and pulsed radiofrequency [PRF]) on thermoregulation. Focusing on hypothalamic function, the effects of local anesthesia, CRF, and PRF on central and peripheral temperatures were analyzed and compared. Our findings revealed that all three nerve block groups cause a decrease in central temperature, with the CRF group exhibiting the most pronounced effect. Furthermore, immunostaining analysis showed decreased neural activity in the preoptic area, suggesting that nerve blocks may influence central thermoregulatory mechanisms. This study provides valuable insights into the effects of peripheral nerve blocks on thermoregulation and may contribute to the development of therapeutic strategies to managing perioperative hypothermia and enhancing pain management, especially in patients undergoing surgeries with high risks of thermoregulatory complications, such as on-pump surgery and laparoscopic surgery.